CYP2D6 Phenotyping Using Urine, Plasma, and Saliva Metabolic Ratios to Assess the Impact of CYP2D6∗10 on Interindividual Variation in a Chinese Population - Pei Hu; Rui Chen; Xin Zheng (Frontiers Media S.A., 2017)
Purpose: Asian populations have around 40-60% frequency of reduced function allele CYP2D6∗10 compared to 1-2% in Caucasian populations. The wide range of CYP2D6 enzyme activities in subjects with the CYP2D6∗10 variant is a big concern for clinical practice. The quantitative analysis measuring the impact of CYP2D6 enzyme activity as a result of one CYP2D6∗10 allele or two CYP2D6∗10 alleles has not been reported in large Asian populations.Methods: A total of 421 healthy Chinese subjects were genotyped for CYP2D6 by polymerase chain reaction and direct DNA sequencing. A total of 235 subjects with CYP2D6∗1/∗1 (n = 22), CYP2D6∗1/∗10 (n = 93), CYP2D6∗10/∗10 (n = 85), and CYP2D6∗5/∗10 (n = 35) were phenotyped for CYP2D6 using dextromethorphan as the probe drug. Metabolic ratios (MR) were calculated as the ratio of parent drug to metabolite in 0-3 h urine, 3 h plasma, and 3 h saliva for each sample type.Results: The urinary, plasma, or salivary MRs increased successively in subjects with CYP2D6∗1/∗1, ∗1/∗10, ∗10/∗10, and ∗5/∗10 (all P < 0.001). In the normal metabolizer group, homozygous CYP2D6∗10/∗10 decreased the CYP2D6 enzyme activity further than heterozygous CYP2D6∗1/∗10. Urinary, plasma, and salivary MRs were highly correlated.Conclusion: The normal metabolizer group calls for a more detailed classification. The activity score system could more accurately predict enzyme activity than by grouping a number of genotypes into a single phenotype group. Single-point plasma samples and saliva samples could be used as alternative phenotyping methods for clinical convenience.